Mean Amplitudes of Vibration of the IF8− Anion - Baran, Enrique José (2008)
The mean amplitudes of vibration of the interesting IF8 − anion (D4d-symmetry), containing iodine (VII), were calculated from known spectroscopic and structural data in the temperature range between 0 and 1000 K. The results are discussed in comparison with those of related species.